Students' Strategies in Learning English Online: A Case Study in a Private Elementary School in Yogyakarta - Hikma Fadilla; Nur Fatimah; Nur Rifai Akhsan (Journal of English Language Teaching and English Linguistics, 2021)
The learning contains activities to achieve certain learning goals. Students have their own strategies to be successful, and they need to be revealed, to be accommodated in the teaching and learning process. The purpose of this study aimed at investigating is to investigate English learning strategies used by fifth grade students of a private school in Yogyakarta in learning English online during pandemic during pandemic period. The research used mixed methods design with forty-one student respondents to the learning strategy questionnaire for quantitative data. Two students were interviewed for qualitative data. The quantitative data from questionnaire was analyzed using descriptive statistic, while the interviews was analyzed using the thematic analysis. The results show that first; first, memory strategy is the type of learning strategies often used by the students under category direct strategies (66.66%), while under indirect category, the respondents applied social strategy most (87.79%). Second, the students have a greater demand to apply direct strategies than indirect one, with percentage as much 23.57% and 14.08% consecutively. Of the two learning strategies, direct and indirect strategies, the learning strategy that is in great demand by fifth grade students is indirect strategies (23.57%) compared to direct strategies (14.08%). The results of the interview showed that the most of the fifth-grade students used writing strategies in the form of sentences in learning English, so that they could easily remember new vocabulary (memory strategies); listening to English music to help students learn English (cognitive strategies); and asking people who are fluent in English when they have difficulty or don't understand English material (social strategies).